Textual Manipulation In National Geographic Indonesia April 2020 Issue - Utama, Luh Gde Titah Madriyanthi; Artawa, Ketut; Udayana, I Nyoman (International Journal of Linguistics and Discourse Analytics, 2021)
This study aims to answer problems that occurred as the implication of the application of strategies in translation. The first began with finding out types of translation strategies in journalistic articles. It is then followed by the analysis of how the faithfulness of the source language text was retained in the target language text. The last would be finding out the types of textual manipulation in the target language text. The object in this study is the National Geographic magazine April 2020 issue, both the English and Indonesian versions. A series of qualitative methods were employed in this study, with the library research technique used in collecting the data. This study also employed the referential method in analyzing the data and formal and informal methods in presenting the analyzed data. The result revealed that Chesterman’s translation strategies which were found in the magazine are syntactic, semantic, and pragmatic strategies. As in the case of the faithfulness of TL towards its SL in the National Geographic Indonesia April 2020 issue, it was found that the faithfulness was retained through the application of Chesterman’s syntactic strategies, as well as textual manipulation through the use of the syntactic strategies